THE EFFECTS OF PROPOLIS ON THE LIVER HISTOPATHOLOGY OF WHITE RATS GIVEN PARACETAMOL - Utami, Alviana Rizqiyah; Berata, I Ketut; Samsuri, Samsuri; Merdana, I Made (Buletin Veteriner Udayana, 2017)
Paracetamol is one of NSAIDs ( Non Steroidal Anti Inflammatory Drugs ) that acts as an analgesic and antipyretic agents but with weak anti-inflammatory activity. Paracetamol has toxic effects to liver in the form of damage to the liver. To prevent the toxic effects of paracetamol, the provision of antioxidants which can protect liver cells damage caused by paracetamol is needed. High antioxidant found in propolis which is widely used at this time. This study used 25 male rats ( Rattus norvegicus ), which consists of five groups. Each treatment group was given standard food and drink. Group 1 (control negative) was given standard food and drink, group 2 (control positive) was given 250 mg/kg body weight of paracetamol orally, group 3 (Pp1) was given 250 mg/kg body weight of paracetamol and each rat was given 0.05 ml of propolis orally, group 4 (Pp2) was given 250 mg/kg body-weight of paracetamol and each rat was given 0.1 ml of propolis orally, and group 5 (Pp3) was given 250 mg/kg body weight of paracetamol and each rat was given 0.15 ml of propolis orally. The treatments were given for 10 days, and on the 11 th day, the necropsy was done to take the livers of the 25 rats for  histopathology preparation. The examined variables included vascular congestion, fatty degeneration, and necrosis with the score (0: no lesions; 1: focal lesions; 2: multifocal lesions; 3: diffuse lesions. Kruskal-Wallis test showed a significant difference on the average of the vascular congestion, fatty degeneration, and necrosis of the tested group. The result of the research, it can be concluded that the 250 mg/kg body weight of Parasetamol can cause liver damage and the 0.15 ml of Propolis for each rat could repair the tissue damage better than the dose of 0.05 ml and 0.1 ml.
Keywords: hepar; parasetamol; propolis